The Ubiquitin Ligase TRIM56 Regulates Innate Immune Responses to Intracellular Double-Stranded DNA - Tsuchida, Tetsuo; Zou, Jian; Saitoh, Tatsuya; Kumar, Himanshu; Abe, Takayuki; Matsuura, Yoshiharu; Kawai, Taro; Akira, Shizuo (Immunity (Cambridge, Mass.), 2010)
The innate immune system detects pathogen- and host-derived double-stranded DNA exposed to the cytosol and induces type I interferon (IFN) and other cytokines. Here, we identified interferon-inducible tripartite-motif (TRIM) 56 as a regulator of double-stranded DNA-mediated type I interferon induction. TRIM56 overexpression enhanced IFN-β promoter activation after double-stranded DNA stimulation whereas TRIM56 knockdown abrogated it. TRIM56 interacted with STING and targeted it for lysine 63-linked ubiquitination. This modification induced STING dimerization, which was a prerequisite for recruitment of the antiviral kinase TBK1 and subsequent induction of IFN-β. Taken together, these results indicate that TRIM56 is an interferon-inducible E3 ubiquitin ligase that modulates STING to confer double-stranded DNA-mediated innate immune responses. ► TRIM56 expression is induced by dsDNA and poly (I:C) stimulation ► TRIM56 enhanced IFN-β promoter activation after dsDNA stimulation ► TRIM56 promoted K63-linked ubiquitination and dimerization of STING ► These modifications are required to form a complex with TBK1 and induce IFN-β